[OP.8D.01] CONTROLLING AND LOWERING BLOOD PRESSURE WITH THE MOBIUSHD DEVICE: FIRST-IN-MAN INTERIM RESULTS (CALM-FIM STUDY). (September 2016) - Spiering, W.; Van Der Heyden, J.; Kroon, A.A.; van den Meiracker, A.H.; Devireddy, C.; Foster, M.T.; Ghali, M.G.H.; Mendelsohn, F.O.; Reuter, H.; Bates, M.C.
Abstract : Objective: To evaluate the safety and performance of the MobiusHD system in patients with resistant hypertension. Design and method: This is a multi-center (9 centers) non-randomized, first-in-man assessment of a nitinol self-expanding rectangular cuboid implant (MobiusHD) designed to increase carotid sinus arterial wall strain without impacting pulsatility or laminar flow. The geometric changes of the carotid sinus enhance baroreceptor sensitivity thus decreasing sympathetic activity and lowering BP. Patients with resistant hypertension (>3 antihypertensives, of which one is a diuretic, and office SBP >160 mmHg), without obstructive carotid disease received a unilateral carotid sinus MobiusHD implant. Incidence of serious adverse events and unanticipated adverse device effects were collected along with changes in blood pressure (BP) measured during 1.5-year follow-up. Results: So far 31 patients, mean age 52 (range 21–76) years, of the anticipated 50 patients received a MobiusHD implant of which 9 patients had failed on renal denervation. Mean pretreatment office BP was 182/107 (±18/15) mmHg with a median of 4.4 prescribed antihypertensives [daily defined dose (DDD): 7.4]. During follow-up 3 patients had serious adverse events (as adjudicated by the data safety monitoring board) related to procedure or device: hypotension (n = 2) and closure device failure, requiring repair (n = 1). At 180 days, 17 of the 20 patients had a reduction in office SBP >10 mmHg and/or 24-hr SBP >5 mmHg. Eight of these 17 patients had a reduction in DDD of antihypertensive medications. Figure. No caption available. Conclusions: So far, implanting the MobiusHD device in patients with resistant hypertension seems to be safe and shows promising results in BP lowering.